The impact of concomitant infective endocarditis in patients with spondylodiscitis and isolated spinal epidural empyema and the diagnostic accuracy of the modified duke criteria - Hijazi, Mido Max; Siepmann, Timo; El-Battrawy, Ibrahim; Aweimer, Assem; Schröttner, Percy; Mirus, Martin; Podlesek, Dino; Schackert, Gabriele; Juratli, Tareq A.; Eyüpoglu, Ilker Y.; Filis, Andreas (Frontiers in Surgery, 2024)
Background The co-occurrence of infective endocarditis (IE) and primary spinal infections (PSI) like spondylodiscitis (SD) and isolated spinal epidural empyema (ISEE) has been reported in up to 30% of cases and represents a life-threatening infection that requires multidisciplinary management to be successful. Therefore, we aimed to characterize the clinical phenotypes of PSI patients with concomitant IE and furthermore to assess the accuracy of the modified Duke criteria in this specific population. Methods We conducted a retrospective cohort study in consecutive SD and ISEE patients treated surgically at our University Spine Center between 2002 and 2022 who have undergone detailed phenotyping comprising demographic, clinical, imaging, laboratory, and microbiologic assessment. Comparisons were performed between PSI patients with IE (PSICIE) and without IE (PSIWIE) to identify essential differences. Results Methicillin-susceptible Staphylococcus aureus (MSSA) was the most common causative pathogen in PSICIE group (13 patients, 54.2%) and aortic valve IE was the most common type of IE (12 patients, 50%), followed by mitral valve IE (5 patients, 20.8%). Hepatic cirrhosis (p < 0.011; OR: 4.383; 95% CI: 1.405–13.671), septic embolism (p < 0.005; OR: 4.387; 95% CI: 1.555–12.380), and infection with Streptococcus spp. and Enterococcus spp. (p < 0.003; OR: 13.830; 95% CI: 2.454–77.929) were identified as significant independent risk factors for the co-occurrence of IE and PSI in our cohort. The modified Duke criteria demonstrated a sensitivity of 100% and a specificity of 66.7% for the detection of IE in PSI patients. Pathogens were detected more frequently via blood cultures in the PSICIE group than in the PSIWIE group (PSICIE: 23, 95.8% vs. PSIWIE: 88, 62.4%, p < 0.001). Hepatic cirrhosis (PSICIE: 10, 41.7% vs. PSIWIE: 33, 21.6%, p = 0.042), pleural abscess (PSICIE: 9, 37.5% vs. PSIWIE: 25, 16.3%, p = 0.024), sepsis (PSICIE: 20, 83.3% vs. PSIWIE: 67, 43.8%, p < 0.001), septic embolism (PSICIE: 16/23, 69.6% vs. PSIWIE: 37/134, 27. 6%, p < 0.001) and meningism (PSICIE: 8/23, 34.8% vs. PSIWIE: 21/152, 13.8%, p = 0.030) occurred more frequently in PSICIE than in PSIWIE patients. PSICIE patients received longer intravenous antibiotic therapy (PSICIE: 6 [4–7] w vs. PSIWIE: 4 [2.5–6] w, p < 0.001) and prolonged total antibiotic therapy overall (PSICIE: 11 [7.75–12] w vs. PSIWIE: 8 [6–12] w, p = 0.014). PSICIE patients spent more time in the hospital than PSIWIE (PSICIE: 43.5 [33.5–53.5] days vs. PSIWIE: 31 [22–44] days, p = 0.003). Conclusions We report distinct clinical, radiological, and microbiological phenotypes in PSICIE and PSIWIE patients and further demonstrate the diagnostic accuracy of the modified Duke criteria in patients with PSI and concomitant IE. In the high-risk population of PSI patients, the modified Duke criteria might benefit from amending pleural abscess, meningism, and sepsis as minor criteria and hepatic cirrhosis as major criterion.